Area Based System Untuk Pemilihan Tanaman Obat Keluarga - Januardy Pratama Bangalino (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2018)
Medicinal plant (toga) is a family of plants that are cultivated by families that have efficacy as a medicine to cure diseases. Area Based System is a system that is intended to provide information to a group of people who are in the area and can be associated with different types of medicinal plant that fit the types of disease spread in the area of residence RT002 /RW001. The main goal of this thesis is to develop a system for providing information on the spread of disease in a shelter residents and to develop the information to help residents provide consideration species of plants of the family in accordance with the diseases. The result of this system is the consideration of medicinal plants that are appropriate to the type of disease that is present in the residence of the citizens.